2005
DOI: 10.1016/j.jana.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Male Self-Disclosure of HIV-Positive Serostatus to Sex Partners: A Review of the Literature

Abstract: HIV-positive men face multiple challenges when deciding whether to disclose their serostatus to sex partners. The purpose of this literature review (1996-2004) is to identify valid and reliable research results that identify factors influencing serostatus disclosure to sex partners by men who are HIV-positive. Articles included in the review were identified through an electronic search using pertinent terms related to disclosure to sex partners, followed by a search of references for additional articles. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
111
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 53 publications
(162 reference statements)
9
111
1
Order By: Relevance
“…With respect to engaging in sexual activity and having multiple sexual partners, the present study was similar to the study by Berniera et al [28] who reported that 23% of the male participants stopped having sex after HIV diagnosis and also, according to Denue et al [25] who reported that, about 39% of HIV patients on ART for a length of time, had multiple sexual partners. Sullivan in his study [29] reported that, as the number of sex partners for men increases, the likelihood of disclosure will decrease. Furthermore, our study was not consistent with a review of studies conducted in Africa by Kennedy et al [30], where it was observed that a majority of HIV patients on ART abstained from sexual activity.…”
Section: Discussionmentioning
confidence: 98%
“…With respect to engaging in sexual activity and having multiple sexual partners, the present study was similar to the study by Berniera et al [28] who reported that 23% of the male participants stopped having sex after HIV diagnosis and also, according to Denue et al [25] who reported that, about 39% of HIV patients on ART for a length of time, had multiple sexual partners. Sullivan in his study [29] reported that, as the number of sex partners for men increases, the likelihood of disclosure will decrease. Furthermore, our study was not consistent with a review of studies conducted in Africa by Kennedy et al [30], where it was observed that a majority of HIV patients on ART abstained from sexual activity.…”
Section: Discussionmentioning
confidence: 98%
“…17 This difficulty is not confined to adolescents; previous studies have recognized that up to one third of sex partners of HIV-infected male adults had not been informed of the diagnosis of HIV infection, with worsening patterns of disclosure with casual partners and with increasing numbers of sexual partners. 18 Thai adults have shown a higher rate of disclosure (88%) to regular sexual partners. 19 Unprotected sexual intercourse, often without disclosing HIV status, has also been reported by about one third of HIV-infected adults in the United States, but the relationship between increased disclosure and safer sexual practices remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8 Men living with HIV have difficulty disclosing their HIV status to their sexual partners, 9 and MSM are less likely to disclose to all of their sexual partners compared to women and heterosexual men. 10 In deciding to disclose, PLHIV weigh the benefits and risks of sharing one's serostatus.…”
mentioning
confidence: 99%